RETENTION AND FAILURE IN DISTANCE EDUCATION: THE EXPERIENCE OF THE NATIONAL TEACHERS INSTITUTE (NTI) KADUNA (1992)
This study sets out to determine the factors leading to wastages among distance learners of the Teachers' Grade II Programme of the National Teachers' Institute Kaduna. This is with a view to finding possible solutions to reducing the failure rate and increase the rate of retention. The data collected through the instruments used were analysed with the chi-square and analyses of variance (ANOVA) to determine the influence of the various factors on the failure and retention rate of the Teachers’ Grade II distance learners. The findings from the study established that: i. the educational background of Teachers1 Grade II distance learners were found inadequate and it greatly affected their retention and failure rate. ii. the course materials significantly affected the learners' rate of retention and failure. iii. the facilitator/tutor factor significantly affected the rate of their retention and failure. iv. the environmental variables were not conducive to learners' need and thus significantly affected the subjects' rate of retention and failure. v. the financial inadequacies of the distance learners grossly affected their rate of retention/ failure. vi. the distance learners' are burdened with too much of social responsibilities and this invariably affected their rate of retention and failure. vii. the motivation available to learners was not adequate and it thus affected the rate of retention and failure. viii that factors like boredome, Professional advancement, learners' welfare, external expectation of learners' and their cognitive ability variedly affected the Teachers' Grade II distance learners. Based on the findings, the following suggestions are made on how distance learning System can sustain learners' interest and improved performance that: i. distance learners should understand the basic concepts and attributes of Distance Education. ii. entry qualification of learners for a particular course of study be uniform. iii. the cost of course materials be highly subsidized by the Government or the employers of the learners. iv. distance learners be motivated and encouraged during the course of their programmes through appropriate reward System in the work place. v. qualified and trained course writers on distance learning System be employed to write course materials for the learners. vi. study centres be adequately equipped with support materials to facilitate better learning environment for the learners. vii. course materials be produced and distributed early enough for the learners use. viii. tutorial masters, Supervisors and others involved in any distance learning Programme be promptly paid their honorarium to motivate them. ix. the various Government policies should take into consideration the implication on the working populace.